2021
DOI: 10.3389/fgene.2021.667382
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Specific Cell Communication Networks Associate With Disease Progression in Cancer

Abstract: The maintenance and function of tissues in health and disease depends on cell–cell communication. This work shows how high-level features, representing cell–cell communication, can be defined and used to associate certain signaling “axes” with clinical outcomes. We generated a scaffold of cell–cell interactions and defined a probabilistic method for creating per-patient weighted graphs based on gene expression and cell deconvolution results. With this method, we generated over 9,000 graphs for The Cancer Genom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…A possible explanation for this in the context of the TME, is the observation that ligand-receptor interactions are not a one-way street. When a ligand-receptor interaction occurs, often this elicits a reaction in both the ligand cell-type, and the receptor cell-type 10 , partially masking the directionality of the interaction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A possible explanation for this in the context of the TME, is the observation that ligand-receptor interactions are not a one-way street. When a ligand-receptor interaction occurs, often this elicits a reaction in both the ligand cell-type, and the receptor cell-type 10 , partially masking the directionality of the interaction.…”
Section: Discussionmentioning
confidence: 99%
“…An unbiased approach to do this consists in the modeling of the TME as a cell-cell communication network, which can be inferred typically from RNA sequencing (RNAseq) data using statistical inference methods or machine learning techniques 6 . Several studies have shown the value of using the reconstructed cell-cell communication networks to study the role of cell-cell communication in the TME [7][8][9][10][11][12] . However, existing techniques have several drawbacks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although more challenging, reconstructing cell-cell interactions from bulk data has the important advantage of being applicable to large available cohorts of tumor samples, with more direct clinical implications. Great advancements in this direction have recently been published, showing the potential of such methods in predicting clinical outcomes [73,74] and response to immunotherapy with checkpoint inhibitors [75,76].…”
Section: Computational Reconstruction Of Cell-cell Interaction Networkmentioning
confidence: 99%
“…The majority of CCI inference methods are designed to analyze CCI for a single condition. As characterizing differences in CCI activity across multiple conditions—for example, between healthy and diseased tissue—helps elucidate the diverse mechanisms of CCI-mediated responses to disease, more so than analyzing condition-specific CCI networks in isolation, recent efforts have focused on developing methodologies to systematically study the differences in CCI between multiple conditions ( Xiong et al, 2019 ; Gibbs et al, 2021 ; Wang et al, 2022 ). However, the majority of previous CCI analyses that analyze differences between conditions tend to analyze CCI networks inferred from a single scRNA-seq sample from each condition or analyze CCI networks constructed by aggregating several samples.…”
Section: Introductionmentioning
confidence: 99%